Microzooplankton grazing impact on the phytoplankton community at a coastal upwelling - Lorena Linacre; J Rubén Lara-Lara; Uriel Mirabal-Gómez; Reginaldo Durazo; Carmen Bazán-Guzmán (Ciencias Marinas, 2017)
Experiments were carried out at a coastal upwelling site (ENSENADA station) off northern Baja California (México) during autumn 2015 (OCT-15) and spring 2016 (APR-16) to estimate phytoplankton daily growth (µo) and mortality (m) rates and to assess microzooplankton grazing impact (m:µo) on the phytoplankton community and specific autotrophic groups. In accordance with regional seasonality and under an environmental warming scenario due to the El Niño 2015–2016 event, significant differences in both hydrographic conditions and the growth–mortality dynamics of the phytoplankton community were observed between the 2 study periods. The µo and m estimates were, respectively, 0.120 ± 0.012 d–1 and 1.145 ± 0.049 d–1 for OCT-15 and 1.186 ± 0.002 d–1 and 0.409 ± 0.086 d–1 for APR-16. The results of this study suggest that the effects of the anomalous warming on the phytoplankton community were more evident in OCT-15. During that period, growth of the larger autotrophic components (diatoms) was severely controlled by the environmental limitation of nutrients caused by the sinking of the thermocline that resulted from the entrance of warm water to the region. Furthermore, microzooplankton exerted active grazing pressure on phytoplankton biomass (72% of chlorophyll a [Chla]) and primary production (PP = 0.20 µg Chla·L–1·d–1), with grazing impact >100% of PP. In APR-16, when the ecosystem apparently started returning to the spring conditions, a high value for PP (3.73 µg Chla·L–1·d–1) was estimated, with only one third of it being consumed by microzooplankton (34% of PP). The results of this research evidence the high dynamism of multivorous food webs coupled to the seasonal and interannual variability of coastal upwelling systems.